A novel manipulator with needle insertion forces feedback for robot‐assisted lumbar puncture. Issue 2 (16th February 2021) - Li, Hongbing; Wang, Yiyun; Li, Yuling; Zhang, Jing
Abstract: Background: The use of lumbar puncture for paediatric diagnosis and treatment, such as cerebrospinal fluid sampling and intracranial pressure measurements, is steadily increasing. However, the standard 'blind' technique makes it difficult to attain accurate needle insertion. Methods: In this study, we developed a robot‐assisted system to improve the precision of needle insertion during lumbar puncture. The manipulator can perform orientation, insertion and rotation of the needle as well as linear motion at targeted locations. We focused on accurately sensing the puncture forces during the needle insertion phase and evaluated the piercing force perception of the operator. Results: The main features of the robot, such as backdrivable joints, physical human–robot cooperation, actuation system with low friction and remote centre of motion mechanism, can enhance overall safety. Conclusions: Experimental results using a lumbar puncture phantom proved that the manipulator could position the needle tip at targeted locations with good accuracy. The data obtained from the test system also showed that the loss of resistance and peak forces for stiff tissues were accurately perceived by the operator.